Lifetime Polyvictimization and Mental Health Outcomes in Women With vs Without Incarceration Histories: A Population-Based Latent Class Analysis - Arévalo, Sandra P. (Violence against women, 2025)
We use latent class analysis, a life course framework, and information on the type, frequency, and timing of trauma exposure to identify distinct polytrauma groups in a national sample of women (AddHealth). We compare the identified polytrauma groups and their associations with mental health in adulthood in women with and without incarceration histories. A unique group with polyvictimization (neglect, physical, sexual) exposure in childhood by a caregiver in women with incarceration histories was not identified in women without incarceration histories. We find evidence of distinct associations between polytrauma groups and mental health and possibly, criminal justice involvement, in adulthood.